Focusing climate negotiations on a uniform common commitment can promote cooperation - Klaus M. Schmidt; Axel Ockenfels (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2021)
International cooperation on the reduction of greenhouse gas emissions, disarmament, or free trade needs to be negotiated. The success of such negotiations depends on how they are designed. In the context of international climate change policy, it has been proposed [e.g., Weitzman J of the Association of Environmental and Resource Economists (2014)] that shifting the negotiation focus to a uniform common commitment (such as a uniform minimum carbon price) would lead to more ambitious cooperation. Yet, a proof-of-concept for this important claim is lacking. Based on game theoretical analyses, we present experimental evidence that strongly supports this conjecture. In our study, human subjects negotiate contributions to a public good. Subjects differ in their benefits and costs of cooperation. Participation in the negotiations and all commitments are voluntary. We consider treatments in which agreements are enforceable, and treatments in which they have to be self-enforcing. In both situations, negotiating a uniform common commitment is more successful in promoting cooperation than negotiating individual commitments (as in the Paris agreement) and complex common commitments that tailor the commitment to the specific situation of each party (as attempted with the Kyoto protocol). Furthermore, as suggested by our model, a uniform common commitment benefits most from being enforced.
Keywords: 330; cooperation; negotiation design; common commitment; reciprocity; climate policy